PREDICTION OF ELASTIC MODULUS FROM COMPESSIVE MODULUS OF LIME STABILIZED LATERITIC SOIL FOR MECHANISTIC DESIGN USING THE SPLIT CYLINDER (International Journal of Engineering and Computer Science, 2014)
In recent years there has been a change in philosophy in flexible pavement design from the more empirical approach to the mechanistic approach based on the elastic theory. The mechanistic approach is in the form of layered elastic theory which is being used by many agencies. Elastic theory based design methods require as input, the elastic properties of these pavement material  for an effective design. In this study  laterites were  gotten from seven (7) local government areas in Rivers state. The laterites were classified using the AASHTO classification system, the properties obtained from the laterites indicates that it is an A-5 soil  which is a silty-clay material. The material was mixed with different lime contents of 0,2,4,6,and 8% and compacted at the energy of Standard Proctor in 100mm diameter by 80mm long split cylindrical moulds, the compacted specimens were moist- cured and tested after 7, 14 ,21 and 28days. The CBR machine was used to load the specimen to failure through static load application. The failure loads as well as the horizontal and vertical strains were measured and used   to predict Elastic modulus from compressive modulus using the SPSS programme, the result show that the Elastic and Compressive modulus increases with an increase in lime content up to 8% lime content, also the predicted values were close to the measured values with an average R2 value of 92%, indicating that the predicted Elastic modulus can be used for mechanistic design of flexible pavement.